Minimum Lagrange Multiplier Unit Root Test with Two Structural Breaks - Lee, Junsoo; Strazicich, Mark C. (The Review of Economics and Statistics, 2003)
The endogenous two-break unit root test of Lumsdaine and Papell is derived assuming no structural breaks under the null. Thus, rejection of the null does not necessarily imply rejection of a unit root per se, but may imply rejection of a unit root without break. Similarly, the alternative does not necessarily imply trend stationarity with breaks, but may indicate a unit root with breaks. In this paper, we propose an endogenous two-break Lagrange multiplier unit root test that allows for breaks under both the null and alternative hypotheses. As a result, rejection of the null unambiguously implies trend stationarity.